Genome-wide identification and in-silico expression analysis of carotenoid cleavage oxygenases gene family in Oryza sativa (rice) in response to abiotic stress - Haider, Muhammad Zeshan; Sami, Adnan; Shafiq, Muhammad; Anwar, Waheed; Ali, Sajid; Ali, Qurban; Muhammad, Sher; Manzoor, Irfan; Shahid, Muhammad Adnan; Ali, Daoud; Alarifi, Saud (Frontiers in Plant Science, 2023)
Rice constitutes a foundational cereal and plays a vital role in the culinary sector.Rice is a fundamental grain and an integral part of the food industry. However, the detriments of abiotic stress on rice quality and productivity are noteworthy. Carotenoid cleavage oxygenases (CCO) hold vital importance as they enable the particular breakdown of carotenoids and significantly contribute towards the growth and response to abiotic stress in rice. Due to the insufficient information regarding rice CCOCCOs and their potential role in abiotic stress, their utilization in stress-resistant genetic breeding remains limited. The current research identified 16 CCOCCO genes within the Oryza sativaOryza sativa japonica group. These OsCCOCCO genes can be bifurcated into three categories based on their conserved sequences: NCEDs (9-Cis-